Cation-Specific Effects on the Self-Assembly of Collagen Molecules Mediated by Acetate on Mica Surface Observed with Atomic Force Microscopy - Zhiwei Wang; Qi Xiao; Xuan Song; Yunfei Wan; Jie Zhu (Journal of Food Quality)
The well-organized collagen layers on mica surface have drawn extensive attention for its essential applications and studies on the process of self-assembly as a model system. In this work, collagen extracted from fish scales by acid-base method was used to explore the self-assembly characters, and atomic force microscopy was applied to observe the collagen assembled on mica surface mediated by acetate with four different cations, including K+, Na+, Mg2+, and Ca2+. It showed that cations might influence the interaction between collagen fibrils and mica surface at high ionic concentration. And a similar network structure was acquired with uniform pore size for four kinds of acetates; nearly ranged collagen fibrils in the same direction were collected in Mg2+ solutions, while flat films with some fibrils were achieved in K+ solutions. The Hofmeister series and Collins’ model were adapted to explain the effects of cations and acetate on the self-assembly of collagen. These results and analysis would be helpful for directing the pattern of collagen assembly on a solid surface with a potential application in food science and engineering.